Heparin removal by ecteola-cellulose pre-treatment enables the use of plasma samples for accurate measurement of anti-Yellow fever virus neutralizing antibodies - Campi-Azevedo, Ana Carolina; Peruhype-Magalhães, Vanessa; Coelho-dos-Reis, Jordana Grazziela; Costa-Pereira, Christiane; Yamamura, Anna Yoshida; Lima, Sheila Maria Barbosa de; Simões, Marisol; Campos, Fernanda Magalhães Freire; de Castro Zacche Tonini, Aline; Lemos, Elenice Moreira; Brum, Ricardo Cristiano; de Noronha, Tatiana Guimarães; et al. (Journal of immunological methods, 2017)
Technological innovations in vaccinology have recently contributed to bring about novel insights for the vaccine-induced immune response. While the current protocols that use peripheral blood samples may provide abundant data, a range of distinct components of whole blood samples are required and the different anticoagulant systems employed may impair some properties of the biological sample and interfere with functional assays. Although the interference of heparin in functional assays for viral neutralizing antibodies such as the functional plaque-reduction neutralization test (PRNT), considered the gold-standard method to assess and monitor the protective immunity induced by the Yellow fever virus (YFV) vaccine, has been well characterized, the development of pre-analytical treatments is still required for the establishment of optimized protocols. The present study intended to optimize and evaluate the performance of pre-analytical treatment of heparin-collected blood samples with ecteola-cellulose (ECT) to provide accurate measurement of anti-YFV neutralizing antibodies, by PRNT. The study was designed in three steps, including: I. Problem statement; II. Pre-analytical steps; III. Analytical steps. Data confirmed the interference of heparin on PRNT reactivity in a dose-responsive fashion. Distinct sets of conditions for ECT pre-treatment were tested to optimize the heparin removal. The optimized protocol was pre-validated to determine the effectiveness of heparin plasma:ECT treatment to restore the PRNT titers as compared to serum samples. The validation and comparative performance was carried out by using a large range of serum vs heparin plasma:ECT 1:2 paired samples obtained from unvaccinated and 17DD-YFV primary vaccinated subjects. Altogether, the findings support the use of heparin plasma:ECT samples for accurate measurement of anti-YFV neutralizing antibodies.